2016
DOI: 10.1103/physrevb.94.155432
|View full text |Cite
|
Sign up to set email alerts
|

Infrared to terahertz optical conductivity ofn-type andp-type monolayerMoS2in the presence of Rashba spin-orbit coupling

Abstract: We investigate the effect of Rashba spin-orbit coupling (SOC) on the optoelectronic properties of nand p-type monolayer MoS 2. The optical conductivity is calculated within the Kubo formalism. We find that the spin-flip transitions enabled by the Rashba SOC result in a wide absorption window in the optical spectrum. Furthermore, we evaluate the effects of the polarization direction of the radiation, temperature, carrier density, and the strength of the Rashba spin-orbit parameter on the optical conductivity. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…However, it should be noted that the effect of trions and possible formation of biexcitons are not considered in our theoretical model. These contributions are possible to be included in a model based on quantum theory, [44] but a more complicated formulation will be encountered.…”
Section: Doi: 101002/pssr202000222mentioning
confidence: 99%
“…However, it should be noted that the effect of trions and possible formation of biexcitons are not considered in our theoretical model. These contributions are possible to be included in a model based on quantum theory, [44] but a more complicated formulation will be encountered.…”
Section: Doi: 101002/pssr202000222mentioning
confidence: 99%
“… m/s denotes the Fermi velocity in a monolayer MoS 2 , is the valley index ( for K and for K′ valley) and denotes the electron with the spin-up (down). meV is the energy gap 12 in the monolayer MoS 2 , is RSOC strength and meV is the spin-splitting energy of the valence band caused by the spin–orbit coupling 12 , 15 . displays the electrostatic potential barrier's height, is a unitary matrix, denotes the unitary matrix, which performs a rotation in the sublattice space 52 and for the monolayer MoS 2 and 53 .…”
Section: Model and Methodsmentioning
confidence: 99%
“…Moreover, the monolayer MoS 2 , in the presence of the Rashba spin–orbit coupling (RSOC), is a fascinating material for spintronics applications. In the monolayer MoS 2 the RSOC can easily be induced and tuned via an external electric field 14 or a ferromagnetic exchange field 15 . On the other hand, the electronic, optical, and transport properties of the monolayer MoS 2 can be modulated by applying an external strain 16 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the spin-conserving intraband transitions give rise to low frequency absorption, whereas the spin-flip transitions result in a wide absorption peak. 29,32 We focus on the optical conductivity due to the inter-band spin flip excitations. As ordinary 2D electron gas systems, 32 it can be shown that the offdiagonal elements of the optical conductivity (transverse or Hall conductivity) are zero in the absence of a magnetic field, i.e.…”
Section: Optical Conductivitymentioning
confidence: 99%
“…The spintronic parameters such as the Rashba coupling strength, electron density and also spin polarization in the 2D materials can be measured optically. [26][27][28][29][30][31][32] Recently, Xiao 29 et al studied the optical conductivity of MoS 2 in the presence of spin-orbit coupling and found that the Rashba spin-orbit parameter can change the absorption peak or window in the optical spectrum. In contrast to the isotropic band structure of MoS 2 the anisotropic band structure in phosphorene results in a highly anisotropic Rashba splitting, 33,34 hence, the strength of spin splitting depends on the direction of k, as well as its magnitude.…”
Section: Introductionmentioning
confidence: 99%